PH-responsive gelatin polymer-coated silica-based mesoporous composites for the sustained-release of indomethacin. Issue 3 (March 2023) - Yu, Bo; Shi, Ruiping; Liu, Chunlai; Liu, Zelong; Shen, Peihang; Hu, Jianglei; Shi, Fengwei
Abstract: This paper prepared drug-loaded mesoporous silica composites with a pH-responsive type. These composites were prepared by using three-dimensional caged silica (SBA-16) as the carrier, 3-aminopropyl trimethoxysilane (APTMS) as the silane coupling agent, and indomethacin (IMC) as the loaded drug, respectively. The drug-loaded precursor NH2 -SBA-16@IMC was prepared by solution diffusion adsorption. Finally, the pH-responsive drug-loaded composites NH2 -SBA-16@IMC@GA were synthesized by wrapping the NH2 -SBA-16@IMC with a condensation polymer of gelatin and glutaraldehyde. The composition and structure of the drug-loaded composites were characterized by FT-IR, XRD, TG, SEM, TEM, and N2 adsorption-desorption. The in vitro simulated release performance of the drug-loaded composites was investigated at 37 °C under three pH conditions. The results show that the NH2 -SBA-16@IMC@GA can be released in response to specific pH environment, which can effectively control the release speed of the indomethacin. Graphical abstract: Image 1 Highlights: NH2 -SBA-16@IMC@GA was synthesized by condensation polymer of gelatin and glutaraldehyde. Indomethacin (IMC) was successfully loaded into the interior of the cage pore. NH2 -SBA-16@IMC@GA was capable of responsive release.